Is the useful field of view a good predictor of at‐fault crash risk in elderly Japanese drivers?. Issue 5 (11th August 2014) - Sakai, Hiroyuki; Uchiyama, Yuji; Takahara, Miwa; Doi, Shun'ichi; Kubota, Fumiko; Yoshimura, Takayoshi; Tachibana, Atsumichi; Kurahashi, Tetsuo
Abstract : Aim: Although age‐related decline in the useful field of view (UFOV) is well recognized as a risk factor for at‐fault crash involvement in elderly drivers, there is still room to study its applicability to elderly Japanese drivers. In the current study, we thus examined the relationship between UFOV and at‐fault crash history in an elderly Japanese population. We also explored whether potential factors that create awareness of reduced driving fitness could be a trigger for the self‐regulation of driving in elderly drivers. Methods: We measured UFOV and at‐fault crash history from 151 community‐dwelling Japanese aged 60 years or older, and compared UFOV of at‐fault crash‐free and crash‐involved drivers. We also measured self‐evaluated driving style using a questionnaire. Results: UFOV in crash‐involved drivers was significantly lower than that in crash‐free drivers. No significant difference was found in self‐evaluated driving style between crash‐free and crash‐involved drivers. In addition, there was no significant association between UFOV and self‐evaluated driving style. Conclusions: The present study showed that UFOV is a good predictor of at‐fault crash risk in elderly Japanese drivers. Furthermore, our data imply that it might be difficult for elderly drivers to adopt appropriate driving strategies commensurate with their current driving competence.Geriatr Gerontol Int 2015; 15: 659–665.